2017
DOI: 10.1016/j.jcot.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-parallel screw fixation for femoral neck fractures in young adults

Abstract: The Authors believes this method provides better union rate & less incidence of femoral neck shortening than that of the conventional inverted triangle screws configuration reported in literature. However multi-center studies & long term follow-up is needed to fully evaluate this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…The laboratory results have been confirmed clinically in two recent studies involving a total of 248 patients with displaced femoral neck fractures. 6,7 These clinical studies have revealed better fixation stability with BDSF, resulting in a lower incidence of nonunion (3.4% 6 and 5% 7 ) and a higher rate of fracture union (96.6% 6 and 95% 7 ) compared with literature data for CFIX.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The laboratory results have been confirmed clinically in two recent studies involving a total of 248 patients with displaced femoral neck fractures. 6,7 These clinical studies have revealed better fixation stability with BDSF, resulting in a lower incidence of nonunion (3.4% 6 and 5% 7 ) and a higher rate of fracture union (96.6% 6 and 95% 7 ) compared with literature data for CFIX.…”
Section: Discussionmentioning
confidence: 84%
“…The nonparallel orientation of the screws does not prevent their sliding in the femoral neck, which can be considered a hollow cylinder from biomechanical point of view. 7…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations